2020
DOI: 10.3389/fgene.2020.00605
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Receptor SF10A (TNFRSF10A) SNPs Correlate With Corticosteroid Response in Duchenne Muscular Dystrophy

Abstract: Background: Duchenne muscular dystrophy (DMD) is a rare and severe X-linked muscular dystrophy in which the standard of care with variable outcome, also due to different drug response, is chronic off-label treatment with corticosteroids (CS). In order to search for SNP biomarkers for corticosteroid responsiveness, we genotyped variants across 205 DMD-related genes in patients with differential response to steroid treatment. Methods and Findings: We enrolled a total of 228 DMD patients with identified dystrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The tumor necrosis factor receptor TNFRSF10A was detected in our study among the top five mutated genes showing multiple deletions, insertions, and point mutations. TNFRSF11A , a member of the same family of genes, was reported in a previous case report of a Gorham-Stout patient [ 3 ] and linked to muscular dystrophy and osteolysis [ 30 , 31 ]. Another example of mutated gene families affecting the same pathway is the missense mutation found in PIK3AP1 (c.1139A > T), which belongs to the PTEN/PI3K/AKT signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor necrosis factor receptor TNFRSF10A was detected in our study among the top five mutated genes showing multiple deletions, insertions, and point mutations. TNFRSF11A , a member of the same family of genes, was reported in a previous case report of a Gorham-Stout patient [ 3 ] and linked to muscular dystrophy and osteolysis [ 30 , 31 ]. Another example of mutated gene families affecting the same pathway is the missense mutation found in PIK3AP1 (c.1139A > T), which belongs to the PTEN/PI3K/AKT signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 828 significant (FDR <0.05) DEGs, including 478 upregulated genes and 350 downregulated genes, were detected between the SP + and SP − myometrium cells ( Table S2 ). The top 10 DEGs enriched in the SP + compared to the SP − were associated with immune response ( XCL2 ( 24 ), CD69 ( 25 ), IL7R ( 26 ), KLRD1 ( 27 ), and IL18R1 ( 28 )) apoptosis ( TNFRSF10A ( 29 )), extracellular matrix ( SPOCK2 ( 30 )) and hematopoietic stem cell ( SELE ( 31 ), GATA3 ( 32 ), CD69 ( 33 ), and VCAM1 ( 34 )) ( Fig. 2D ).…”
Section: Resultsmentioning
confidence: 99%
“…103–105 The sample size ranged from 64 105 to 449 52 among the studies that reported the sample size. The studied genotypes were possible contributory single nucleotide polymorphisms (SNPs) in the SPP1 , 52,92,95,97,100–102,104,106 LTBP4 , 43,52,92,97–99,102,106 THBS1 , 52,99 ACTN3, 52,103 ADRB2, 93 CD40 52,92,94 , TCTEX1D1 , 96 human leukocyte antigen (HLA), 105 and TNFRSF10A 102 gene regions identified by genome-wide association studies to modify the dystrophinopathy phenotypes. Other SNPs that were tested and not significant or that appeared in only one article are not reported here.…”
Section: Resultsmentioning
confidence: 99%
“…The recessive LTBP4 haplotype (IAAM/IAAM) showed a correlation with longer time to loss of ambulation for individuals treated with glucocorticoids 92,98,106 but was not confirmed in other studies. 22,97,102,104 The LBTP4 haplotype was not associated with cardiomyopathy 43,92 or pulmonary function. 52 The LTBP4 rs10880 TT genotype was found to delay the loss of ambulation with additional protective effects when paired with glucocorticoid treatment in individuals of White heritage 92 and is also shown to be cardioprotective in combination with steroid use.…”
Section: Characteristics Associated With Modifier Genesmentioning
confidence: 87%
See 1 more Smart Citation